Crédito PRONAF: conquista, afirmação e reconhecimento: o processo de formulação de uma política pública - Domingues, Alexandre Pires (2008)
Brazil is a huge country full of peculiar significant issues for those who want to make academic contributions for public policy making and implementation. Therefore, this work aims to contribute to the public policy making debate from the family farmers perspective. Starting with historical issues about Brazilian rural policy, this text highlights the National Program for Familiar Agriculture (PRONAF) credit policy and several relevant elements for the public administration on this specific field such as the Sistema Nacional de Crédito Rural (60¿s), the sector crisis on the 80¿s and the implementation of the PRONAF itself. The theoretical reference is based on several works related to policy making, especially under authors as Lindblom and Kingdon, based on the model build by Barzelay and Velarde which focus on the public policy processes. For the conclusion, some nuances are mentioned as developing needs such as policy appropriation, social actor movements and policy rebuilding itself